Мастер: эффективность управленческой деятельности - Поздняков Владимир Яковлевич (Удмуртия, 1988)
Экземпляры: КР (20020330) / Инвентарный номер: у37574 / Сис.шифр: 65.050.9(2)2 / Авт.знак: П 47 / ГРНТИ: 82 / ББК: 65.301-212